In silico testing of a multimaterial scaffold for mandibular reconstruction - Rebolo, Pedro; Orassi, Vincenzo; Areias, Bruno; Checa, Sara; Ramião, Nilza; Correia, Jaime Filipe; Rendenbach, Carsten; Natal, Renato; Parente, Marco (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMandibular reconstruction following segmental resection is a challenging procedure. The implantation of scaffolds as an alternative for microsurgical free flaps appears as a promising strategy; however, there is still a lack of understanding of how such scaffolds should be designed to support bone regeneration. This study investigates the influence of scaffold design and its mechanical properties on the biomechanical conditions induced in mandibular reconstruction.MethodsA 3D finite element model of the human mandible was developed, and a large bone defect scenario was simulated, with physiological post-operative loading and boundary conditions. The large defect was bridged with a scaffold, supported by a titanium mesh, and stabilized with a load-bearing titanium fixation plate. To study the effect of the fixation device stiffness on the induced biomechanical conditions within the scaffold pores, two different materials were tested for the fixation device, namely, a Ti-6Al-4V titanium alloy and a polylactic acid (PLA). In addition, three different strut-based scaffold architectures were investigated with different strut orientations, while keeping the same strut diameter and similar overall porosity. Two types of material distributions through the scaffold were also studied. The first type was a hydrogel-based scaffold, whereas the second type was a multimaterial type where the scaffold was divided into three equal volume parts: in the center, a hydrogel material was employed, and in the extremities, a ceramic material. These combinations of two fixation materials and three scaffold architectures with two combination materials resulted in 12 experimental groups.Results and DiscussionNo failure was predicted in the fixation devices for any of the configurations investigated. The PLA fixation device induced higher strains within the healing region than the titanium fixation device. Differences in scaffold architecture did not influence the strain levels within the healing region. Changes in the scaffold material distribution led to considerable differences in the mechanical strains within the scaffold pores. The multimaterial scaffold induced higher strains within the healing region than the only hydrogel scaffold, which might be beneficial to promote bone healing in the defect. Thus, a multimaterial scaffold seems to be able to provide a more suitable biomechanical environment to support bone regeneration, especially in large segmental defects. Future studies should focus on the mechanobiological optimization of the scaffold design and its fixation system in different clinical scenarios.